Mentoring and Training in Writing Scientific Articles Through Mind Mapping Strategies and Accredited Scientific Publications as an Effort to Improve Teacher Professionalism at MA Ummul Quro Al-Islami - Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The aim of implementing this service is to find out the success in applying mind mapping strategies in writing scientific articles for MA Ummul Quro Al-Islami teachers. The method of implementing this service is implementing service for MA Ummul Quro Al-Islami teachers to increase their professional rank through training in writing scientific articles using the Mind Mapping strategy. The approach used in this service is the PAR (Participatory Action Research) approach. According to Agus Afandi, the stages of using the PAR approach are the to Know stage, the to Understand stage, the to Plan stage, the to Act stage, and the to Change stage. The results of implementing this service, namely Mentoring and Training in Scientific Article Writing through the Mind Mapping Strategy, showed significant results. These results are shown by the results of writing scientific articles which have an average score of 77%. This means that this value describes that teachers are able to write scientific articles after learning through mind mapping strategies. Likewise, the results show proof of submitting articles in several accredited and national journals. The conclusion from this service is that it has succeeded in making changes to the ability to write scientific articles.